Real-life clinical practice and management of polysensitized patients with respiratory allergies: a large, global survey of clinicians prescribing allergen immunotherapy. (4th March 2017) - Wahn, Ulrich; Calderon, Moises A.; Demoly, Pascal
ABSTRACT: Background: The allermix survey was conducted to gain insights into the most frequently diagnosed allergies worldwide, the use of allergen immunotherapy (AIT) in clinical practice, and to identify current clinical approaches for the management of polyallergic patients. Methods: The survey was conducted in 19 countries worldwide during 2016. Clinicians currently prescribing AIT completed an online questionnaire, designed to gather data on their daily clinical practice, most commonly diagnosed and treated allergies among their patients, awareness and adherence to recommendations and guidelines on AIT, the AIT format(s) that they choose to prescribe, and management of polyallergic patients. Results: Respondents ( N  = 1029) considered a clinical demonstration of safety and effectiveness, and quality and standardization of allergen extract, as key factors influencing their choice of which AIT formulation to prescribe. 98% of respondents reported managing polyallergic patients; 58% were treated with single-allergen AIT and 42% with multiple-allergen AIT. 74% of respondents were aware of latest AIT practice guidelines, while 67% had an awareness of recent recommendations for pharmaceutical manufacturers. Conclusion: These findings highlight the need for high-quality AIT products that are supported by robust efficacy and safety data, and address the treatment habits of allergy specialists in their real-life clinical practice.